Volume 1A, Symposia: Turbomachinery Flow Simulation and Optimization; Applications in CFD; Bio-Inspired and Bio-Medical Fluid M 2016
DOI: 10.1115/fedsm2016-7590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shear Stress on the Growth Rate of Micro-Organisms in Agitated Reactors

Abstract: The effects of hydrodynamic shear stress on the growth rate of cyanobacteria Synechocystis sp. and Chlamydomonas reinhardtii microalgae cells were studied in agitated photobioreactors, since they have different motility rates and sizes. An experimental setup was designed and constructed to monitor the growth rate of the micro-organisms versus the shear rate; experiments were carried out in a well controlled environment, under constant atmospheric pressure and 20 °C temperature. Digitally controlled magnetic ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The growth rate of cyanobacteria has been observed to increase with shear stress, probably by promoting orientation and increasing the contact area of the microorganisms and nutrients [73,74]. For the Cyano-EPS a certain degree of shear stress will be necessary once the rheology of the medium is altered and the mass and gas transfers become less efficient throughout the time.…”
Section: Process Conditionsmentioning
confidence: 99%
“…The growth rate of cyanobacteria has been observed to increase with shear stress, probably by promoting orientation and increasing the contact area of the microorganisms and nutrients [73,74]. For the Cyano-EPS a certain degree of shear stress will be necessary once the rheology of the medium is altered and the mass and gas transfers become less efficient throughout the time.…”
Section: Process Conditionsmentioning
confidence: 99%
“…48 Because the biofilm built by EPS around the cells is very weak 47 and possesses poor resistance to high hydrodynamic stress, the microalgal cells can be easily damaged under a high agitation speed. On the other, a low agitation speed weakened turbulent mixing, and then decreased the CO 2 or air mass transfer coefficient from gas phase to liquid phase (culture medium) 49 ; it also influenced light distribution 17 and as a result inhibited biomass growth. Thus, biomass growth was optimal under middle agitation speeds.…”
Section: Eps Production and Cell Aggregationmentioning
confidence: 99%
“…In other recent research, the effects of fluid shear stress were studied for the cyanobacteria and green algae strains Synechocystis sp. and Chlamydomonas reinhardtii, in 150 ml cultures (Fadlallah et al, 2016). In this study, the growth rate of Detrimental impacts of turbulent mixing have also been demonstrated, with inhibition attributed to cell disruption from shear stress (Chalmers, 2015;Han & Yuan, 2004;Kunnen, Malas, Semeins, Bakker, & Peters, 2017;Richardson, Lannigan, & Macara, 2015;Sieck et al, 2014Sieck et al, , 2013Wang, Lü, Mao, & Long, 2014;Yi et al, 2010).…”
Section: Introductionmentioning
confidence: 52%
“…Turbulent cultivation environments induce physiological responses in microalgae in raceways and photobioreactors (Fadlallah et al, 2016; Havens, James, East, & Smith, 2003; Kumar, Dasgupta, Nayak, Lindblad, & Das, 2011; Michels, van der Goot, Norsker, & Wijffels, 2010; Mirón et al, 2003; Moisander, Hench, Kononen, & Paerl, 2002; Nguyen & Hoang, 2016; Xiao, Li, Li, Zhang, & Guo, 2016). For example, Xiao et al (2016) studied the effects of turbulence dissipation rates ranging from 0 to 0.08 m 2 ·s −3 in 1‐L cultures (Xiao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation